The Utilization of Generative AI in Designing Data Analytics and Visualization Workshop (Case Study: GDGoC at Universitas Negeri Malang) - Refiana Andiyah; Ence Surahman; Herlina Ike Oktaviani (International Journal of Computer Science and Humanitarian AI, 2025)
This study explores the use of Generative Artificial Intelligence (Generative AI) in designing a Data Analytics and Visualization workshop within the Google Developer Groups on Campus (GDGoC) community at the State University of Malang. Employing a qualitative case study approach, data were gathered through in-depth interviews, observations, and document analysis involving key informants directly engaged in the planning and execution of the workshop. The findings reveal that Generative AI significantly enhanced the efficiency, effectiveness, and quality of the workshop program. The technology was utilized across various stages, from conceptualizing the event and gathering references to preparing presentation materials. Respondents noted that Generative AI facilitated faster and more systematic material organization, supporting prior research on its ability to improve productivity and efficiency in educational settings. Nevertheless, the study also identified challenges, including reliance on AI, difficulties in generating appropriate prompts, and the necessity of validating AI-generated content. In the context of Human-Computer Interaction (HCI), Generative AI was perceived to offer favorable usability and user experience, although adequate digital literacy is essential to ensure its ethical and effective use. In conclusion, Generative AI presents considerable potential as a tool for developing training programs, with human involvement remaining critical to ensure the relevance and accuracy of the generated information.